Precise control of pore hydrophilicity enabled by post-synthetic cation exchange in metal–organic frameworks. Issue 15 (3rd April 2018) - Wright, Ashley M.; Rieth, Adam J.; Yang, Sungwoo; Wang, Evelyn N.; Dincă, Mircea
Abstract : The ability to control the relative humidity at which water uptake occurs in a given adsorbent is advantageous, making that material applicable to a variety of different applications. Abstract : The ability to control the relative humidity at which water uptake occurs in a given adsorbent is advantageous, making that material applicable to a variety of different applications. Here, we show that cation exchange in a metal–organic framework allows precise control over the humidity onset of the water uptake step. Controlled incorporation of cobalt in place of zinc produces open metal sites into the cubic triazolate framework MFU-4 l, and thereby provides access to materials with uptake steps over a 30% relative humidity range. Notably, the MFU-4 l framework has an extremely high water adsorption capacity of 1.05 g g −1, amongst the highest known for porous materials. The total water capacity is independent of the cobalt loading, showing that cation exchange is a viable route to increase the hydrophilicity of metal–organic frameworks without sacrificing capacity.